2008
DOI: 10.1128/mcb.01251-07
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of R-Loop Formation at Immunoglobulin Class Switch Sequences

Abstract: R-loops have been described in vivo at the immunoglobulin class switch sequences and at prokaryotic and mitochondrial origins of replication. However, the biochemical mechanism and determinants of R-loop formation are unclear. We find that R-loop formation is nearly eliminated when RNase T 1 is added during transcription but not when it is added afterward. Hence, rather than forming simply as an extension of the RNA-DNA hybrid of normal transcription, the RNA must exit the RNA polymerase and compete with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 48 publications
4
136
1
Order By: Relevance
“…A likely candidate for this structure is an extended R loop, in which the nascent RNA rehybridizes with the template DNA strand behind the elongating RNAP. Indeed, evidence for the formation of R loops was obtained for transcripts containing G stretches, i.e., when extrastable RNA/DNA duplex was formed (11). R-loop formation could exacerbate transcriptional blockage by preventing the rewinding of a DNA duplex upstream of the RNA polymerase, which contributes to transcription elongation (29,30).…”
Section: Mechanism Of Transcription Blockage By G N ∕C N Sequences Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely candidate for this structure is an extended R loop, in which the nascent RNA rehybridizes with the template DNA strand behind the elongating RNAP. Indeed, evidence for the formation of R loops was obtained for transcripts containing G stretches, i.e., when extrastable RNA/DNA duplex was formed (11). R-loop formation could exacerbate transcriptional blockage by preventing the rewinding of a DNA duplex upstream of the RNA polymerase, which contributes to transcription elongation (29,30).…”
Section: Mechanism Of Transcription Blockage By G N ∕C N Sequences Anmentioning
confidence: 99%
“…The increased stability of rPu/dPy duplexes is likely responsible for stable R-loop formation by these sequences (11), although alternative DNA structures might also be involved (8,12,13).…”
mentioning
confidence: 99%
“…It has been hypothesized that switch regions have evolved to contain frequent AGCT sequences, which contains WRC hotspots on both strands, to promote a high level of deamination (22). These potential hotspots are interspersed in otherwise G-rich clusters in the template strands that have been demonstrated to promote R-loop formation, exposing a single-stranded DNA substrate (44,45).…”
Section: Loop Graft Variants Effectively Restrict Hiv-bhagwat and Co-mentioning
confidence: 99%
“…To explore the mechanism by which AID-mediated Top1 reduction augments S region cleavage and CSR, we speculated that aberrant supercoiling by Top1 protein reduction may induce non-B DNA structure in the S region so that Top1 cannot religate, resulting in irreversible cleavage by Top1. DNA structural alterations can be estimated by the DNA's sensitivity to bisulfite modification from dC to dU, which occurs in the single-stranded regions (6,7). The presence of consecutive C bases is suitable for determining the single-strandedness by the bisulfite assay (7).…”
Section: Top1mentioning
confidence: 99%
“…The S region transcripts seem to remain on the DNA template for a short period, thus facilitating the formation of R-loop. Lieber and colleagues reported that the bisulfite treatment of nuclear DNA from switch-induced spleen cells converted dC to dU in the S region, indicating the presence of single stranded DNA in the S region in activated B cells (6,7). R-loop may not survive long but lead to the formation of non-B structures including stem-loop, cruciform, and triplex in the S region because of abundant inverted repeats (3,(8)(9)(10).…”
mentioning
confidence: 99%